Sex Differences, Estrogen Metabolism and Signaling in the Development of Pulmonary Arterial Hypertension - Sun, Yanan; Sangam, Shreya; Guo, Qiang; Wang, Jian; Tang, Haiyang; Black, Stephen M.; Desai, Ankit A. (Frontiers in Cardiovascular Medicine, 2021)
Pulmonary arterial hypertension (PAH) is a complex and devastating disease with a poor long-term prognosis. While women are at increased risk for developing PAH, they exhibit superior right heart function and higher survival rates than men. Susceptibility to disease risk in PAH has been attributed, in part, to estrogen signaling. In contrast to potential pathological influences of estrogen in patients, studies of animal models reveal estrogen demonstrates protective effects in PAH. Consistent with this latter observation, an ovariectomy in female rats appears to aggravate the condition. This discrepancy between observations from patients and animal models is often called the “estrogen paradox.” Further, the tissue-specific interactions between estrogen, its metabolites and receptors in PAH and right heart function remain complex; nonetheless, these relationships are essential to characterize to better understand PAH pathophysiology and to potentially develop novel therapeutic and curative targets. In this review, we explore estrogen-mediated mechanisms that may further explain this paradox by summarizing published literature related to: (1) the synthesis and catabolism of estrogen; (2) activity and functions of the various estrogen receptors; (3) the multiple modalities of estrogen signaling in cells; and (4) the role of estrogen and its diverse metabolites on the susceptibility to, and progression of, PAH as well as their impact on right heart function.